(untitled) (Journal of Environmental Science and Natural Resources, 2013)
A study was conducted to evaluate the status of heavy metal contaminations of drainage water of Dhaka Metropolitan City. The water samples were collected from four major drains of Dhaka metropolitan city during February to March, 2008. The chemical analysis of water samples (pH, EC, As, Cu, Mn, ’ln. Pb and Cd) was conducted at the Central Laboratory of Bangladesh Agricultural University, Mymensingh. The chemical concentrations of drain water were: in case of pH = 5.13, in case of EC = 33.36 (?scm-1), in case of Cu = 0.129 ppm, in case of Zn = 1.276 ppm, in case of Mn = 0.109 ppm, in case of As = 0.036 ppb, in case of = Pb 0.004 ppm, and in case of Cd = 0.228 ppm. The average pH value of drain water ranged from 4.96 to 5.34 and the mean was 5.138, which was an indicating of strong acidic in nature. The mean EC value of drainage water was recorded 33.363 ?Scm-1, all the water samples indicated low to medium salinity. According to drinking water (Potable water) and public water standard, Mn, and Cd toxicity were detected in drain water. According to WHO for aquaculture standard Mn and Cd were harmful level for all living organism. Some water were found unsuitable due to higher concentration of Mn over the recommended limit but other ions like Zn, As, and Pb were within the safe limit. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14566 J. Environ. Sci. & Natural Resources, 5(2): 11-14 2012